LEGAL MECHANISMS FOR PREVENTING TEAM CONFLICTS AS A TOOL FOR IMPROVING THE EFFICIENCY OF ENTERPRISE PERSONNEL MANAGEMENT (INNOVATIVE ECONOMY, 2026)
Bortnik N.V. LEGAL MECHANISMS FOR PREVENTING TEAM CONFLICTS AS A TOOL FOR IMPROVING THE EFFICIENCY OF ENTERPRISE PERSONNEL MANAGEMENTPurpose. The aim of the article is to substantiate the theoretical and methodological foundations for using legal mechanisms to prevent team conflicts as a tool for improving the efficiency of enterprise personnel management.Methodology of research. The study applies a set of general scientific and special research methods. The method of theoretical generalization was used to clarify the essence of team conflict as a managerial and legal phenomenon. Analysis and synthesis were applied when studying scientific works and legal acts related to mobbing, mediation, labour disputes, and conflict management. The method of systematization made it possible to group legal mechanisms for preventing team conflicts according to legislative, contractual, local regulatory, procedural, monitoring, educational and preventive levels. The structural and functional approach was used to identify the functions of these mechanisms in the personnel management system, while logical modelling was applied to develop an integrated model for preventing team conflicts at the enterprise. The method of scientific abstraction was used to formulate conclusions on the role of legal mechanisms in improving the efficiency of personnel management. The theoretical basis of the research includes Ukrainian labour legislation, mediation legislation, and modern Ukrainian scientific works on mobbing, non-judicial settlement of labour disputes, conflict management at the enterprise, business communication, and HR management.Findings. The article clarifies the essence of team conflict as a managerial and legal phenomenon that arises in the process of joint labour activity and affects productivity, quality of communication, social and psychological climate, employee engagement, and organizational resilience of the enterprise. It is substantiated that legal mechanisms for preventing team conflicts should not be considered only as a means of legal response to violations of labour rights, since they perform preventive, organizational, communicative, protective, and economic functions in the personnel management system. The legal mechanisms for preventing team conflicts are systematized according to legislative, contractual, local regulatory, procedural, monitoring, educational and preventive levels. An integrated model for preventing team conflicts at the enterprise is proposed, which involves the formalization of interaction rules, prevention of conflict-generating situations, early detection of tension, use of mediation procedures, restoration of team interaction, and organizational learning.Originality. The scientific novelty lies in substantiating an interdisciplinary approach to legal mechanisms for preventing team conflicts as a tool for improving the efficiency of enterprise personnel management. Unlike approaches in which conflict is considered mainly as a psychological or legal problem, the article proves its managerial and economic content and substantiates the need to integrate legal mechanisms into enterprise HR processes.Practical value. The practical value of the findings lies in the fact that they can be used by organisations to improve their internal human resources management systems, particularly when developing corporate policies on the prevention of workplace bullying, codes of ethical conduct, internal mediation procedures, and regulations governing the handling of employee enquiries and complaints.Key words: legal mechanisms, human resources management, team conflict, workplace bullying, mediation, HR management, organisational communication.
Keywords: legal mechanisms; human resources management; team conflict; workplace bullying; mediation; HR management; organisational communication